A review on Tradescantia: phytochemical constituents, biological activities and health-promoting effects - Butnariu, Monica; Quispe, Cristina; Herrera-Bravo, Jesús; Fernández-Ochoa, Álvaro; Emamzadeh-Yazdi, Simin; Adetunji, Charles Oluwaseun; Memudu, Adejoke Elizabeth; Otlewska, Anna; Bogdan, Paulina; Antolak, Hubert; Tamimi, Katayoun; Baghalpour, Navid; et al. (IMR Press, 2022)
Tradescantia is a genus of herbaceous and perennial plants belonging to the Commelinaceae family and organized into three infrageneric classifications and 12 sections. More than 80 species within the genus have been used for centuries for medicinal purposes. Phytochemical compounds (from various species of the genus) such as coumarins, alkaloids, saponins, flavonoids, phenolics, tannins, steroids and terpenoids have recently been characterized and described with antioxidant, cytotoxic, anti-inflammatory, anticancer or antimicrobial properties. The objective of this review is to describe the different aspects of the genus Tradescantia, including its botanical characteristics, traditional uses, phytochemical composition, biological activities, and safety aspects.